Análisis del manejo integrado de Sibine spp en el cultivo de Palma Aceitera (Elaeis guineensis Jacq) - Muñoz Peralta, George Damián (2021)
The oil palm (Elaeis guineensis Jacq) in Ecuador is a crop that has first generated a great economic impact, socially due to the high demand for its products and by-products, the oil palm cultivation is subject to different pests that attack regardless of the age of the crop and not the time of year, it is important to highlight the integrated pest management (MIP) where it allows us to apply different control methods allowing us a growth and productive development, thus generating a good production and performance as a whole. with all the right chores. Among these most important lepidopterans that attack the oil palm crop is the Sibine sp species and the Sibine spp species that attack the oil palm are Sibine megasomoides Walker and Sibine fusca, they belong to the limacodidae family since the larvae attack mainly the epidermis on the underside of the leaflets causing small gnawing, ending up devouring the entire leaf blade until leaving only the midrib. Integrated pest management in oil palm cultivation allows pest damage to be kept below the economically acceptable level. (MIP) is a combination of various control measures that reduces the risk to human health and the effects on the environment from the farm. For the management of insect pests and pathogens, it is important to know their biology, behavior and the environment where they develop, which will facilitate the application of controls, appropriately combining genetic, regulatory, cultural, biological, physical and chemical resources.